Normative values for circulating intestinal fatty acid binding protein and calprotectin across gestational ages - Darla R. Shores; Jennifer Fundora; Mitzi Go; Fauzia Shakeel; Sandra Brooks; Samuel M. Alaish; Jun Yang; Chhinder P. Sodhi; David J. Hackam; Allen Everett (BMC, 2020)
Abstract Background Necrotizing enterocolitis (NEC) is associated with significant morbidity and mortality. Serum biomarkers to aid diagnosis, such as intestinal fatty acid binding protein (IFABP) and calprotectin, are actively being investigated; however, the normative values of these markers among healthy premature and term infants remains unknown. We sought to identify normative values for the serum concentrations of IFABP and calprotectin across gestational (GA) and post-menstrual age. Methods We collected serum from infants (24-40 weeks GA) in the first week of life and at multiple time points in a sub-cohort of premature infants (24-29 weeks GA), excluding sepsis or known intestinal disease. IFABP and calprotectin were measured using ELISA. Groups were compared with descriptive statistics and mixed effects linear regression. Results One hundred twelve infants had specimens in the first week of life, and 19 premature infants had longitudinal specimens. IFABP concentration in the first week of life was low and did not differ across gestational ages. Longitudinally, IFABP increased 4% per day (P < 0.001). Calprotectin concentration in the first week of life was more variable. An inverse relationship between day of life and calprotectin level was found in the longitudinal cohort (P < 0.001). Conclusions Serum IFABP and calprotectin fluctuate over time. Infants had low levels of IFABP during the first week of life, independent of gestational age, and levels increased longitudinally in premature infants. Calprotectin levels generally declined over time. Normative data for infants is necessary to establish meaningful cut-off levels for clinical use.